Structural diversity in a stereotypic organelle — Sensory cilia of Caenorhabditis elegans. Issue 6 (10th June 2022) - Maurya, Ashish K.
Abstract: Sensory cilia, an ancient organelle, displays a high degree of conservation in its structure and functioning. Sensory cilia also fulfill a wide range of sensory functions, from sensing environmental signals (light, sound, chemicals, and mechanical forces) to interpreting intercellular developmental signals. One way they appear to fulfill these diverse and specialized roles is by adopting a variety of shapes and sizes. We are only beginning to document and appreciate this complexity. Here in this review, using the varied and specialized cilia found on Caenorhabditis elegans sensory neurons, I highlight some of the most obvious examples of this structural diversity and the underlying mechanisms if known. Such structural diversity appears to arise from the modulation of deeply conserved molecular pathways and also from cell‐ and species‐specific mechanisms. Studying these ciliary specializations will thus provide for a comprehensive understanding of ciliary biology and might uncover understudied aspects of ciliary disease biology. Abstract : Top‐Comparing cilia shape of simple vs complex cilia in C. elegans. Bottom‐Contribution iof CCRK‐RCK kinase cascade in cilia elaboration in a complex AWA cilia.